A purification process for producing ethanol from synthesis gas

Adsorbent fillers with high specific surface area and porosity were prepared by modifying materials such as bentonite and fly ash, which solved the problem of high moisture and impurities content in the preparation of ethanol in synthesis gas, and achieved high purity purification of ethanol products.

CN118851881BActive Publication Date: 2025-02-11ANHUI CARBON XIN TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411323791.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-02-11
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

In the prior art, during the distillation process, methyl acetate is azeotroped with water and ethanol, resulting in a high content of moisture and impurities in the product, making it difficult to improve the purity.

Method used

By combining modified bentonite and modified fly ash with starch, sodium silicate and other substances, an adsorbent precursor with porous structures is prepared, and a large specific surface area and porosity are prepared by modification of chitosan and zinc oxide. The hydrophilic adsorbent filler is used to purify ethanol on the column plate of the distillation tower.

Benefits of technology

The specific surface area and porosity of the adsorbent filler are improved, the adsorption capacity of water and impurities is enhanced, the moisture and impurities content in ethanol products are reduced, and the purity of ethanol is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118851881B_ABST
    Figure CN118851881B_ABST
Patent Text Reader

Abstract

The invention discloses a purification process for preparing ethanol from synthesis gas, belongs to the technical field of ethanol purification, and is used to solve the technical problem that the porosity and specific surface area of ​​adsorbent fillers in the prior art are low, and the purity of ethanol products prepared by distillation and purification of crude ethanol prepared from synthesis gas needs to be further improved. The invention comprises the following steps: modified bentonite, modified fly ash, starch and sodium silicate are uniformly mixed and added into a reactor, and deionized water is added into the reactor. The invention prepares a porous hydrophilic adsorbent precursor by compounding modified bentonite, modified fly ash, starch, sodium silicate and sodium aluminate, modifies the precursor by chitosan and zinc oxide, prepares a hydrophilic adsorbent filler with large specific surface area and porosity, and then optimizes the ethanol distillation and purification process in the prior art, reduces the content of impurities such as water, methanol and acetate in the ethanol product, and prepares a high-purity industrial ethanol product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ethanol purification, and in particular to a purification process for preparing ethanol from synthesis gas. Background Art

[0002] The route of using solid coal and coke to gasify synthesis gas and then preparing low-carbon alcohols through the synthesis gas is not only efficient, clean and sustainable, but also effectively improves the utilization rate of coal resources.

[0003] In the prior art, methanol is first produced from synthesis gas, and methanol is dehydrated to produce dimethyl ether, and then the process of producing ethanol through carbonylation of dimethyl ether and hydrogenation of methyl acetate avoids the problem of acetic acid corroding the equipment, reduces the requirements for equipment materials, and because the difficulty of hydrogenation of methyl acetate is lower than that of acetic acid, the hydrogenation catalyst is mainly a non-precious metal catalyst with Cu as the active component, which is inexpensive. Therefore, the cost of this route is low and the economic competitiveness is strong;

[0004] However, the prepared ethanol is mixed with unreacted methanol, methyl acetate, methyl formate, water and other alcohol by-products generated during the reaction. The prior art often uses a distillation tower to purify crude ethanol, and uses the boiling point difference of molecules to separate impurities in ethanol from ethanol. However, methyl acetate and water contained in the crude ethanol prepared from synthesis gas will azeotrope with ethanol in the distillation tower. The packed tower often uses molecular sieves as fillers, which have low porosity and specific surface area, and poor hydrophilicity and selective adsorption of methanol and acetate. The water content in the prepared ethanol product is high, and the purity of the ethanol product needs to be further improved.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The object of the present invention is to provide a purification process for preparing ethanol from synthesis gas, which is used to solve the technical problems that the adsorbent filler in the prior art has low porosity and specific surface area, poor hydrophilicity and selective adsorption of methanol and acetate, and the ethanol product purified by distillation of crude ethanol prepared from synthesis gas has high contents of water, methanol and methyl acetate, and the purity of the ethanol product needs to be further improved.

[0007] The object of the present invention can be achieved by the following technical scheme: A purification process for preparing ethanol from synthesis gas comprises the following steps:

[0008] S1. Modified bentonite, modified fly ash, starch and sodium silicate are mixed uniformly and added to a reactor, deionized water is added to the reactor, stirred at room temperature for 30-50 minutes, the temperature of the reactor is increased to 70-80° C., sodium aluminate solution is added to the reactor, stirred for 90-110 minutes, and the solvent is evaporated under reduced pressure to obtain a slurry with a water content of 10-20%, and granulated and calcined to obtain an adsorbent precursor;

[0009] The synthetic reaction principle of the adsorbent precursor is:

[0010] After the modified bentonite, modified fly ash, starch and sodium silicate are uniformly mixed, deionized water is added and stirred. The raw materials undergo preliminary physical mixing and wetting under the action of water molecules. At the same time, sodium silicate dissolves in water to form silicate ions. At high temperature (70-80°C), the aluminate ions in the sodium aluminate solution react with silicate ions, calcium ions, aluminum ions and the like in the reaction system to undergo complex chemical reactions including ion exchange, precipitation formation, complexation reaction and the like, thereby increasing the intermolecular force. By evaporating most of the aqueous solution, as the water content decreases, the interaction between the reaction products increases. Granulation is performed in a granulator to form a particle body with a certain strength and structure. After further solidification of the particle body through a programmed temperature increase treatment, the decomposition of organic matter (starch) and the rearrangement and sintering of inorganic mineral phases are promoted to form a more compact and stable structure, thereby making the structure of the particle body more stable, and preparing an adsorbent precursor with a porous structure.

[0011] S2, adding chitosan and glacial acetic acid solution to a reactor, stirring until the system is dissolved, adding adsorbent precursor and zinc oxide to the reactor, ultrasonically dispersing for 30-50 minutes, dripping sodium hydroxide solution into the reactor, ultrasonically dispersing for 40-60 minutes after the dripping is completed, and post-processing to obtain an adsorbent filler;

[0012] The synthetic reaction principle of adsorbent filler is:

[0013] During the reaction, chitosan and zinc oxide are dissolved in glacial acetic acid solution, and ultrasonic dispersion is used to promote uniform mixing of chitosan, zinc oxide and adsorbent precursor. When sodium hydroxide solution is added at any time, the pH of the system increases, and the amino groups in the chitosan molecules begin to remove protons and restore their original neutral or negatively charged state. The chitosan molecules interact with the porous structure of the adsorbent precursor through hydrogen bonds, electrostatic interactions or van der Waals forces to form a chitosan coating layer. Under alkaline conditions, cross-linking reactions may occur between chitosan molecules to form a three-dimensional network structure on the adsorbent precursor. Moreover, under alkaline conditions, zinc ions coordinate or chelate with functional groups such as hydroxyl and amino groups in chitosan molecules to form a stable complex. The solid and liquid in the reaction mixture are separated by suction filtration, and the filter cake is washed with purified water to neutrality to remove residual sodium hydroxide and other soluble impurities. Subsequently, during the high-temperature drying process, the water is gradually evaporated, and the interaction between the solid particles is further enhanced to form an adsorbent filler with a stable structure and performance.

[0014] S3, placing the adsorbent filler on the tower plate of the distillation tower to form an adsorbent bed on the tower plate of the distillation tower;

[0015] S4. The crude ethanol is transported from the feed pipe to the interior of the distillation tower. After purification and distillation in the distillation tower, the finished ethanol is discharged from the discharge pipe of the distillation tower, the light components are discharged from the vent pipe at the top of the distillation tower, and the heavy components collected at the inner bottom of the distillation tower are discharged from the bottom discharge pipe of the distillation tower.

[0016] Further, in step S1, the amount ratio of the modified bentonite, modified fly ash, starch, sodium silicate, deionized water and sodium aluminate solution is 7g:3g:0.6-0.8g:3.5g:12-14mL:10g, and the sodium aluminate solution is composed of sodium aluminate and deionized water in a weight ratio of 1:9. The roasting method is as follows: the granulated particles are placed in a muffle furnace, the temperature of the muffle furnace is increased to 95-105°C at a heating rate of 3-5°C / min, and the heat treatment is carried out for 50-70min, the temperature of the muffle furnace is increased to 180-220°C at a heating rate of 1-3°C / min, and the heat treatment is carried out for 30-40min, and the temperature of the muffle furnace is increased to 6-9 The temperature is raised to 450-550°C at a heating rate of ℃ / min, and the mixture is kept warm for 2-3h, and then cooled to room temperature naturally to obtain an adsorbent precursor. In step S2, the amount ratio of chitosan, glacial acetic acid solution, adsorbent precursor, zinc oxide, and sodium hydroxide solution is 1-1.5g:50mL:10g:0.1-0.15g:60mL, the mass fraction of the glacial acetic acid solution is 3-5%, and the concentration of sodium hydroxide is 0.8-1.2mol / L. The post-treatment includes: after the reaction is completed, filtering, washing the filter cake with purified water until it is neutral and then drying, transferring the filter cake to a drying oven at a temperature of 90-100°C, and drying to constant weight to obtain an adsorbent filler.

[0017] Furthermore, the number of plates of the distillation tower is 60, the height of the adsorbent bed on each plate is 7-10 cm, one end of the feed pipe extending into the interior of the distillation tower is located at the top of the 13th plate from bottom to top, and one end of the discharge pipe extending into the interior of the distillation tower is located at the top of the 54th plate from bottom to top. The reflux ratio inside the distillation tower is 60, and the distillate feed ratio is 0.105-0.110.

[0018] Further, the modified bentonite is processed by the following steps:

[0019] A1. Add activated bentonite and calcium oxide into a ball mill, mill for 40-60 min, and pass through a 100-mesh sieve to obtain a mixed powder;

[0020] A2. Add the mixed powder and deionized water into a reactor and stir for 30-50 minutes at room temperature to obtain a mixture;

[0021] A3. Spread the mixed material in a constant temperature and humidity chamber for 10-12 hours of heat preservation and moisture retention, and obtain modified bentonite after post-treatment.

[0022] The synthetic reaction principle of modified bentonite is:

[0023] Through ball milling dispersion, calcium oxide is mixed and dispersed with activated bentonite in a physically embedded manner. Calcium oxide is an alkaline oxide, which will hydrolyze in water to generate calcium hydroxide. At this time, the calcium hydroxide has been adsorbed to the interlayer active center of the activated bentonite. In the heat preservation and moisture retention treatment stage under constant temperature and humidity conditions, the calcium hydroxide generated by the hydrolysis of calcium oxide further promotes the dissolution and reprecipitation of silicate minerals in the bentonite, avoiding the hydration effect of the hydroxide ions of calcium hydroxide, resulting in the aggregation of calcium hydroxide in the outer pores of the activated bentonite. Calcium hydroxide cannot diffuse into the pores of the activated bentonite, and the alkaline calcium hydroxide is loaded inside and outside the pores of the activated bentonite to prepare a modified bentonite.

[0024] Furthermore, in step A1, the weight ratio of the activated bentonite and calcium oxide is 5:2; in step A2, the amount ratio of the mixed powder and deionized water is 1g:2mL; in step A3, the temperature of the constant temperature and humidity chamber is 65-75°C, and the humidity is 50-60%. The post-treatment includes: after the treatment is completed, the temperature of the constant temperature and humidity chamber is reduced to room temperature, the material is discharged to obtain a crude modified bentonite product, the crude modified bentonite product and deionized water are added to a reactor at a dosage ratio of 1g:20mL, stirred and dispersed for 60-80min, filtered, the filter cake is rinsed with deionized water and then dried, and the filter cake is transferred to a drying oven at a temperature of 60-70°C, vacuum dried to constant weight, and passed through a 100-mesh sieve to obtain modified bentonite.

[0025] Furthermore, the preparation method of activated bentonite is: adding bentonite and hydrochloric acid into a reaction kettle and stirring, raising the temperature of the reaction kettle to 75-85° C., keeping the temperature and stirring for 4-6 hours, and post-treating to obtain activated bentonite.

[0026] The synthetic reaction principle of activated bentonite is:

[0027] Bentonite is mainly composed of layered silicate minerals such as montmorillonite, and its structure contains exchangeable cations (such as sodium, calcium, magnesium, etc.) and interlayer water. These layered structures make bentonite have good adsorption, expansion and cation exchange capacity. Hydrochloric acid is a less corrosive inorganic acid. Through the concentration of carbonate acid, while avoiding excessive reaction caused by high concentration acid, the exchange reaction between hydrogen ions and cations between bentonite layers can be carried out at a relatively moderate rate, so that the hydrogen ions in the hydrochloric acid and the cations between the bentonite layers undergo ion exchange reaction, and the cations such as sodium, potassium, and magnesium are converted into soluble salts of acid and dissolved, weakening the original interlayer bond force, cracking the layered lattice of bentonite, unblocking the pores of bentonite, and enhancing the activity of bentonite.

[0028] Furthermore, the usage ratio of the bentonite and the hydrochloric acid is 1g:10mL, the mass fraction of the hydrochloric acid is 10-12%, and the post-treatment in the preparation method of the activated bentonite includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the filter is filtered, the filter cake is washed with purified water until it is neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 70-80°C, and dried to constant weight to obtain activated bentonite.

[0029] Furthermore, the preparation method of the modified fly ash is as follows: adding fly ash and modifying liquid into a reactor and stirring, lowering the temperature of the reactor to 18-22° C., keeping the temperature and stirring for 120-160 minutes, and post-treating to obtain the modified fly ash.

[0030] The synthetic reaction principle of modified fly ash is:

[0031] Fly ash is mainly composed of oxides and silicate minerals of elements such as silicon, aluminum, and iron, and its surface usually has certain charges and active sites. In an alkaline environment, the anions of sodium carbonate and sodium hydroxide will react with the cations (such as silicon and aluminum cations) on the surface of fly ash, and soluble salts such as sodium silicate and sodium aluminate will be activated through dissociation or hydrolysis reactions to form ions or molecular forms that are more easily reactive. The activated monomers approach each other and are connected by chemical bonds to form small aggregates or "cores". As the reaction proceeds, more monomers are added to these cores, making the aggregates gradually larger. Cross-linking reactions may also occur between different aggregates, forming a three-dimensional network structure on the surface of fly ash, increasing the specific surface area and porosity of fly ash.

[0032] Furthermore, the dosage ratio of the fly ash and the modifying liquid is 1g:15mL, the modifying liquid is composed of sodium carbonate, sodium hydroxide and deionized water in a dosage ratio of 5g:1g:50mL, and the post-treatment in the preparation method of the modified fly ash includes: after the reaction is completed, filtering, washing the filter cake with deionized water until it is neutral and then drying, transferring the filter cake to a drying oven at a temperature of 85-95°C, drying to constant weight, and passing through a 100-mesh sieve to obtain modified fly ash.

[0033] The present invention has the following beneficial effects:

[0034] 1. The purification process for preparing ethanol from synthesis gas provided by the present invention comprises the following steps: loading alkaline calcium hydroxide on activated bentonite to prepare modified bentonite and modified fly ash, starch, and sodium silicate, mixing the prepared materials with sodium aluminate, and preparing an adsorbent filler through subsequent granulation, roasting, and other treatments. During the preparation process, the modified fly ash and modified bentonite break the original structure of the raw materials to form more micropores and mesopores, thereby increasing the specific surface area and porosity of the adsorbent filler. The larger specific surface area and porosity are conducive to sufficient contact between the adsorbent and the adsorbate, thereby increasing the adsorption efficiency, promoting the separation of methanol, methyl acetate, and ethanol in crude ethanol, and preparing a high-purity ethanol product. Moreover, during the preparation process, the adsorbent filler optimizes the structure of the adsorbent to make it have stronger hydrophilicity, so that the adsorbent filler has better performance in removing water from crude ethanol, optimizes the existing ethanol distillation and purification process parameters, can effectively remove moisture from crude ethanol, reduce the water content of the ethanol product, and obtain high-purity industrial ethanol.

[0035] 2. The purification process for preparing ethanol from synthesis gas provided by the present invention comprises the following steps: modifying bentonite with hydrochloric acid to improve the porosity and activity of the activated bentonite; and then premixing the activated bentonite with calcium oxide solid, and then performing humidification curing to further dissociate the calcium hydroxide and release a large amount of hydroxide ions. These hydroxide ions are adsorbed on the surface of the bentonite or enter its pore structure, and the hydroxide ions can form hydrogen bonds with water molecules, thereby enhancing the interaction between the material and water, and further improving the hydrophilicity of the modified bentonite. According to XRD analysis, only the intensity of the diffraction peak of the fly ash changes before and after the modification, and no obvious new diffraction peak appears. The mineral types of the fly ash do not change before and after the modification. The silicate in the fly ash usually has a complex network structure, which is formed by covalently connecting silicon and oxygen atoms to form a three-dimensional skeleton. Sodium hydroxide is a strong base, and hydrogen When sodium oxide contacts fly ash, the hydroxide ions dissociated from the sodium oxide in the aqueous solution attack the silicon-oxygen bonds or silicon-aluminum bonds in the silicate network, releasing silicate ions or aluminate ions. At the same time, the hydroxide ions recombine with these ions to form new compounds containing hydroxyl groups, thereby further improving the hydrophilicity of the modified fly ash. Combined with its own high porosity, the adsorbent filler exhibits good porosity. The high porosity helps to reduce the diffusion resistance of the adsorbate molecules inside the adsorbent, allowing them to reach the adsorption site faster, thereby improving the adsorption efficiency. In addition, the increase in porosity means that there are more tiny spaces inside the adsorbent, thereby increasing the surface area of ​​the adsorbent. The increased surface area provides more adsorption sites for impurities to adsorb, allowing the adsorbent to more effectively promote the separation of ethanol products from impurities and improve the purity of ethanol.

[0036] 3. The purification process of ethanol produced from synthesis gas provided by the present invention, in the mixed system of modified bentonite, modified fly ash, starch, and sodium silicate, silicate substances such as sodium silicate can form silica gel in water, and the addition of sodium aluminate may further promote the gelation process, tightly combine the components together to form an adsorbent precursor with a porous structure, and promote the close combination of the components after drying. Starch, as a natural polymer compound, has good adhesion and film-forming properties. In the reaction system, starch can be used as a binder to more tightly combine inorganic particles such as modified bentonite and modified fly ash and adhesives such as sodium silicate to form a more uniform and stable slurry. During the heating process, starch will be carbonized to form a carbonaceous material with adsorption activity. The adsorbent precursor is carbonized to produce microporous or mesoporous structures, thereby increasing the specific surface area and porosity of the adsorbent precursor, and further improving the separation and purification effect of the adsorbent filler on crude ethanol. Chitosan is a natural high molecular weight polysaccharide with abundant functional groups such as hydroxyl and amino groups, which can form hydrogen bonds or other interactions with water molecules, methanol and acetate, thereby enhancing the adsorption capacity of the adsorbent filler for these impurities. The surface of zinc oxide has abundant active sites for selective adsorption of methanol and acetate impurity molecules. Chitosan and zinc oxide cooperate in the adsorbent filler, and the porous structure and adsorption sites provided by chitosan are combined with the selective adsorption capacity of zinc oxide, thereby jointly improving the separation effect of the adsorbent filler on impurities such as water, methanol, acetate, etc. in crude ethanol. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 It is a structural schematic diagram of the distillation tower in the present invention;

[0039] Figure 2 The XRD analysis spectra of fly ash and modified fly ash in the present invention are shown in FIG.

[0040] Figure 3 It is the infrared analysis spectrum of the activated bentonite and the modified bentonite in the present invention.

[0041] In the figure: 100, methanol distillation tower; 200, feed pipe; 300, discharge pipe; 400, vent pipe; 500, discharge pipe. DETAILED DESCRIPTION

[0042] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Example 1

[0044] This embodiment provides a method for preparing an adsorbent filler for purifying ethanol from synthesis gas, comprising the following steps:

[0045] S1. Preparation of modified fly ash

[0046] Sodium carbonate, sodium hydroxide and deionized water were mixed evenly in a dosage ratio of 5 g:1 g:50 mL to obtain a modified solution;

[0047] Weigh: 1000g of fly ash and 15000mL of modified liquid are added to the reactor and stirred. The temperature of the reactor is lowered to 18°C, and the mixture is kept warm and stirred for 120min. After the reaction is completed, the filter is filtered and the filter cake is washed with deionized water until it is neutral and then dried. The filter cake is transferred to a drying oven at 85°C, dried to constant weight, and passed through a 100-mesh sieve to obtain modified fly ash.

[0048] S2. Preparation of activated bentonite

[0049] Weigh: 1000 g of bentonite and 10000 mL of 10 wt% hydrochloric acid, add into the reactor and stir, raise the temperature of the reactor to 75°C, keep warm and stir for 4 hours, after the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 70°C, dry to constant weight, and obtain activated bentonite.

[0050] S3. Preparation of modified bentonite

[0051] Weigh: 1000 g of activated bentonite and 400 g of calcium oxide, add them into a ball mill, ball mill for 40 min, and pass through a 100-mesh sieve to obtain a mixed powder;

[0052] The mixed powder and deionized water were added into the reactor at a ratio of 1 g:2 mL, and stirred at room temperature for 30 min to obtain a mixture;

[0053] The mixed material was spread in a constant temperature and humidity chamber, the temperature was set to 65°C, the humidity was set to 50%, and the heat preservation and moisture retention treatment was carried out for 10 hours. The temperature of the constant temperature and humidity chamber was lowered to room temperature, and the material was discharged to obtain a crude modified bentonite product;

[0054] The modified bentonite crude product and deionized water were added into the reactor at a ratio of 1g:20mL, stirred and dispersed for 60min, filtered, the filter cake was rinsed with deionized water and then dried, and the filter cake was transferred to a drying oven at a temperature of 60°C, vacuum dried to constant weight, and passed through a 100-mesh sieve to obtain modified bentonite.

[0055] S4. Preparation of adsorbent precursor

[0056] Mixing sodium aluminate and deionized water in a weight ratio of 1:9 to obtain a sodium aluminate solution;

[0057] Weigh: 1400g of modified bentonite, 600g of modified fly ash, 120g of corn starch and 700g of sodium silicate, mix well and add to the reactor, add 2400mL of deionized water to the reactor, stir at room temperature for 30min, raise the temperature of the reactor to 70°C, add 2000g of sodium aluminate solution to the reactor, stir for 90min, evaporate the solvent under reduced pressure to obtain a slurry with a water content of 10%, granulate to obtain a spherical particle body with a particle size of 3-5mm, put the particle body into a muffle furnace, increase the temperature of the muffle furnace to 95°C at a heating rate of 3°C / min, and keep warm for 50min, increase the temperature of the muffle furnace to 180°C at a heating rate of 1°C / min, and keep warm for 30min, increase the temperature of the muffle furnace to 450°C at a heating rate of 6°C / min, keep warm for 2h, and naturally cool to room temperature to obtain an adsorbent precursor.

[0058] S5. Preparation of adsorbent filler

[0059] Weigh: 100 g of chitosan and 5000 mL of 3 wt% glacial acetic acid solution, add them to the reactor, stir until the system is dissolved, add 1000 g of adsorbent precursor and 10 g of zinc oxide to the reactor, ultrasonically disperse for 30 min, add 6000 mL of 0.8 mol / L sodium hydroxide solution dropwise to the reactor, after the addition is completed, ultrasonically disperse for 40 min, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at 90°C, and dry to constant weight to obtain an adsorbent filler.

[0060] Example 2

[0061] This embodiment provides a method for preparing an adsorbent filler for purifying ethanol from synthesis gas, comprising the following steps:

[0062] S1. Preparation of modified fly ash

[0063] Sodium carbonate, sodium hydroxide and deionized water were mixed evenly in a dosage ratio of 5 g:1 g:50 mL to obtain a modified solution;

[0064] Weigh: 1000g of fly ash and 15000mL of modified liquid are added to the reactor and stirred. The temperature of the reactor is lowered to 20°C, and the mixture is kept warm and stirred for 140 minutes. After the reaction is completed, the filter is filtered and the filter cake is washed with deionized water until it is neutral and then dried. The filter cake is transferred to a drying oven at 90°C, dried to constant weight, and passed through a 100-mesh sieve to obtain modified fly ash.

[0065] S2. Preparation of activated bentonite

[0066] Weigh: 1000 g of bentonite and 10000 mL of 11 wt% hydrochloric acid, add into the reactor and stir, raise the temperature of the reactor to 80°C, keep warm and stir for 5 hours, after the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 75°C, dry to constant weight, and obtain activated bentonite.

[0067] S3. Preparation of modified bentonite

[0068] Weigh: 1000 g of activated bentonite and 400 g of calcium oxide, add them into a ball mill, ball mill for 50 min, and pass through a 100-mesh sieve to obtain a mixed powder;

[0069] The mixed powder and deionized water were added into the reactor at a dosage ratio of 1 g:2 mL, and stirred at room temperature for 40 min to obtain a mixture;

[0070] The mixed material was spread in a constant temperature and humidity chamber, the temperature was set to 70°C, the humidity was set to 55%, and the heat preservation and moisture retention treatment was carried out for 11 hours. The temperature of the constant temperature and humidity chamber was lowered to room temperature, and the material was discharged to obtain a crude modified bentonite product;

[0071] The modified bentonite crude product and deionized water were added into the reactor at a ratio of 1g:20mL, stirred and dispersed for 70min, filtered, the filter cake was rinsed with deionized water and then dried, and the filter cake was transferred to a drying oven at a temperature of 65°C, vacuum dried to constant weight, and passed through a 100-mesh sieve to obtain modified bentonite.

[0072] S4. Preparation of adsorbent precursor

[0073] Mixing sodium aluminate and deionized water in a weight ratio of 1:9 to obtain a sodium aluminate solution;

[0074] Weigh: 1400g of modified bentonite, 600g of modified fly ash, 140g of cassava starch and 700g of sodium silicate, mix well and add to the reactor, add 2600mL of deionized water to the reactor, stir at room temperature for 40min, raise the temperature of the reactor to 75°C, add 2000g of sodium aluminate solution to the reactor, stir for 100min, evaporate the solvent under reduced pressure to obtain a slurry with a water content of 15%, granulate to obtain a spherical particle body with a particle size of 3-5mm, put the particle body into a muffle furnace, increase the temperature of the muffle furnace to 100°C at a heating rate of 4°C / min, and keep it warm for 60min, increase the temperature of the muffle furnace to 200°C at a heating rate of 2°C / min, and keep it warm for 35min, increase the temperature of the muffle furnace to 500°C at a heating rate of 7.5°C / min, and keep it warm for 2.5h, and naturally cool to room temperature to obtain an adsorbent precursor.

[0075] S5. Preparation of adsorbent filler

[0076] Weigh: 150 g of chitosan and 5000 mL of 5 wt% glacial acetic acid solution, add them to the reactor, stir until the system is dissolved, add 1000 g of adsorbent precursor and 15 g of zinc oxide to the reactor, ultrasonically disperse for 50 min, add 6000 mL of 1.2 mol / L sodium hydroxide solution dropwise to the reactor, after the addition is complete, ultrasonically disperse for 60 min, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at 100 ° C, and dry to constant weight to obtain an adsorbent filler.

[0077] Example 3

[0078] This embodiment provides a method for preparing an adsorbent filler for purifying ethanol from synthesis gas, comprising the following steps:

[0079] S1. Preparation of modified fly ash

[0080] Sodium carbonate, sodium hydroxide and deionized water were mixed evenly in a dosage ratio of 5 g:1 g:50 mL to obtain a modified solution;

[0081] Weigh: 1000g of fly ash and 15000mL of modified liquid are added to the reactor and stirred. The temperature of the reactor is lowered to 22°C, and the mixture is kept warm and stirred for 160min. After the reaction is completed, the filter is filtered and the filter cake is washed with deionized water until it is neutral and then dried. The filter cake is transferred to a drying oven at 95°C, dried to constant weight, and passed through a 100-mesh sieve to obtain modified fly ash.

[0082] S2. Preparation of activated bentonite

[0083] Weigh: 1000 g of bentonite and 10000 mL of 12 wt% hydrochloric acid, add into the reactor and stir, raise the temperature of the reactor to 85°C, keep warm and stir for 6 hours, after the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at 80°C, dry to constant weight, and obtain activated bentonite.

[0084] S3. Preparation of modified bentonite

[0085] Weigh: 1000 g of activated bentonite and 400 g of calcium oxide, add them into a ball mill, ball mill for 60 min, and pass through a 100-mesh sieve to obtain a mixed powder;

[0086] The mixed powder and deionized water were added into the reactor at a ratio of 1 g:2 mL, and stirred at room temperature for 50 min to obtain a mixture;

[0087] The mixed material was spread in a constant temperature and humidity chamber, the temperature was set to 75°C, the humidity was set to 60%, and the heat preservation and moisture retention treatment was carried out for 12 hours. The temperature of the constant temperature and humidity chamber was lowered to room temperature, and the material was discharged to obtain a crude modified bentonite product;

[0088] The modified bentonite crude product and deionized water were added into the reactor at a ratio of 1g:20mL, stirred and dispersed for 80min, filtered, the filter cake was rinsed with deionized water and then dried, and the filter cake was transferred to a drying oven at a temperature of 70°C, vacuum dried to constant weight, and passed through a 100-mesh sieve to obtain modified bentonite.

[0089] S4. Preparation of adsorbent precursor

[0090] Mixing sodium aluminate and deionized water in a weight ratio of 1:9 to obtain a sodium aluminate solution;

[0091] Weigh: 1400g of modified bentonite, 600g of modified fly ash, 160g of wheat starch and 700g of sodium silicate, mix well and add to the reactor, add 2800mL of deionized water to the reactor, stir at room temperature for 50min, raise the temperature of the reactor to 80°C, add 2000g of sodium aluminate solution to the reactor, stir for 110min, evaporate the solvent under reduced pressure to obtain a slurry with a water content of 20%, granulate to obtain a spherical particle body with a particle size of 3-5mm, put the particle body into a muffle furnace, increase the temperature of the muffle furnace to 105°C at a heating rate of 5°C / min, and keep warm for 70min, increase the temperature of the muffle furnace to 220°C at a heating rate of 3°C / min, and keep warm for 40min, increase the temperature of the muffle furnace to 550°C at a heating rate of 9°C / min, and keep warm for 3h, and naturally cool to room temperature to obtain an adsorbent precursor.

[0092] S5. Preparation of adsorbent filler

[0093] Weigh: 150 g of chitosan and 5000 mL of 5 wt% glacial acetic acid solution, add them to the reactor, stir until the system is dissolved, add 1000 g of adsorbent precursor and 15 g of zinc oxide to the reactor, ultrasonically disperse for 50 min, add 6000 mL of 1.2 mol / L sodium hydroxide solution dropwise to the reactor, after the addition is complete, ultrasonically disperse for 60 min, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at 100 ° C, and dry to constant weight to obtain an adsorbent filler.

[0094] Example 4

[0095] This embodiment provides a purification process for preparing ethanol from synthesis gas, comprising the following steps:

[0096] Step 1, a plate tower with 60 plates is selected as the distillation tower 100, and a feed pipe 200 and a discharge pipe 300 connected to the interior of the distillation tower 100 are arranged on the outer wall of the distillation tower 100, one end of the feed pipe 200 extending to the interior of the distillation tower 100 is located at the top of the 13th plate from bottom to top, and one end of the discharge pipe 300 extending to the interior of the distillation tower 100 is located at the top of the 54th plate from bottom to top, a vent pipe 400 is arranged at the top of the distillation tower 100, and a discharge pipe 500 is arranged at the bottom of the distillation tower 100;

[0097] Step 2: Fill the adsorbent filler prepared in Example 1 onto the plates of the distillation tower 100 to form an adsorbent bed layer with a thickness of 7 cm on the top of each plate of the distillation tower 100;

[0098] Step 3: transport the crude ethanol from the feed pipe 200 to the interior of the distillation tower 100. The reflux ratio inside the distillation tower 100 is 60, and the distillate feed ratio is 0.105. After purification and distillation in the distillation tower 100, the finished ethanol is discharged from the discharge pipe 300 of the distillation tower 100, and the light components are discharged from the top vent pipe 400 of the distillation tower 100. The heavy components collected at the inner bottom of the distillation tower 100 are discharged from the bottom discharge pipe 500 of the distillation tower 100.

[0099] Example 5

[0100] This embodiment provides a purification process for preparing ethanol from synthesis gas, comprising the following steps:

[0101] Step 1, a plate tower with 60 plates is selected as the distillation tower 100, and a feed pipe 200 and a discharge pipe 300 connected to the interior of the distillation tower 100 are arranged on the outer wall of the distillation tower 100, one end of the feed pipe 200 extending to the interior of the distillation tower 100 is located at the top of the 13th plate from bottom to top, and one end of the discharge pipe 300 extending to the interior of the distillation tower 100 is located at the top of the 54th plate from bottom to top, a vent pipe 400 is arranged at the top of the distillation tower 100, and a discharge pipe 500 is arranged at the bottom of the distillation tower 100;

[0102] Step 2: Fill the adsorbent filler prepared in Example 2 onto the plates of the distillation tower 100 to form an adsorbent bed layer with a thickness of 8.5 cm on the top of each plate of the distillation tower 100;

[0103] Step 3: transport the crude ethanol from the feed pipe 200 to the interior of the distillation tower 100. The reflux ratio inside the distillation tower 100 is 60, and the distillate feed ratio is 0.107. After purification and distillation in the distillation tower 100, the finished ethanol is discharged from the discharge pipe 300 of the distillation tower 100, and the light components are discharged from the vent pipe 400 at the top of the distillation tower 100. The heavy components collected at the inner bottom of the distillation tower 100 are discharged from the bottom discharge pipe 500 of the distillation tower 100.

[0104] Example 6

[0105] This embodiment provides a purification process for preparing ethanol from synthesis gas, comprising the following steps:

[0106] Step 1, a plate tower with 60 plates is selected as the distillation tower 100, and a feed pipe 200 and a discharge pipe 300 connected to the interior of the distillation tower 100 are arranged on the outer wall of the distillation tower 100, one end of the feed pipe 200 extending to the interior of the distillation tower 100 is located at the top of the 13th plate from bottom to top, and one end of the discharge pipe 300 extending to the interior of the distillation tower 100 is located at the top of the 54th plate from bottom to top, a vent pipe 400 is arranged at the top of the distillation tower 100, and a discharge pipe 500 is arranged at the bottom of the distillation tower 100;

[0107] Step 2: Fill the adsorbent filler prepared in Example 3 onto the plates of the distillation tower 100 to form an adsorbent bed layer with a thickness of 10 cm on the top of each plate of the distillation tower 100;

[0108] Step 3: transport the crude ethanol from the feed pipe 200 to the interior of the distillation tower 100. The reflux ratio inside the distillation tower 100 is 60, and the distillate feed ratio is 0.110. After purification and distillation in the distillation tower 100, the finished ethanol is discharged from the discharge pipe 300 of the distillation tower 100, and the light components are discharged from the top vent pipe 400 of the distillation tower 100. The heavy components collected at the inner bottom of the distillation tower 100 are discharged from the bottom discharge pipe 500 of the distillation tower 100.

[0109] Comparative Example 1

[0110] The difference between this comparative example and Example 6 is that, when preparing the adsorbent filler prepared in Example 3, step S1 is omitted, and the fly ash in step S1 replaces the modified fly ash in step S4.

[0111] Comparative Example 2

[0112] The difference between this comparative example and Example 6 is that, when preparing the adsorbent filler prepared in Example 3, step S2 is omitted, and the modified bentonite in step S3 is replaced by the bentonite in step S2.

[0113] Comparative Example 3

[0114] The difference between this comparative example and Example 6 is that when preparing the adsorbent filler prepared in Example 3, in step S3, a mixed solution consisting of 400 g of calcium hydroxide and 2800 mL of water and 1000 g of activated bentonite are stirred and mixed to prepare a mixing material.

[0115] Comparative Example 4

[0116] The difference between this comparative example and Example 6 is that when the adsorbent filler prepared in Example 3 is prepared, zinc oxide is not added in step S5.

[0117] Performance Test:

[0118] The specific surface area and porosity of the adsorbent fillers used in Examples 4-6 and Comparative Examples 1-4 were tested with reference to the standard GB / T 21650.1-2008 "Mercury Intrusion Porosimetry and Gas Adsorption Method for Determination of Pore Size Distribution and Porosity of Solid Materials Part 1: Mercury Intrusion Porosimetry". The specific test results are shown in Table 1.

[0119] The mass fraction of static water adsorption and the dynamic water adsorption rate of the adsorbent fillers used in Examples 4-6 and Comparative Examples 1-4 were tested with reference to the standard GB / T 6287-2021 "Determination of static water adsorption of molecular sieves". The specific test results are shown in Table 1;

[0120] The moisture, methanol, acetate and ethanol contents in the finished ethanol prepared in Examples 4-6 and Comparative Examples 1-4 were tested with reference to the standard GB / T 6820-2016 "Ethanol for Industrial Use". The specific test results are shown in Table 2.

[0121] Table 1 - Performance test data of adsorbent filler

[0122]

[0123] Table 2-Quality test data of finished ethanol

[0124]

[0125] Data Analysis:

[0126] Comparing the data in Table 1 and Table 2 above, the specific surface area of ​​the adsorbent filler prepared by the present invention reaches 815m 2 / g, the porosity reaches 66.2%, and the static water adsorption capacity reaches 46.2%. The adsorbent filler is used as a filler in a packing tower to distill and purify ethanol prepared from synthesis gas, and the prepared ethanol content reaches 99.81%, the moisture content is reduced to 0.04%, the methanol content is reduced to 18.7 mg / L, and the acetate content is reduced to 96.7 mg / L. All performance parameters are better than those of the comparative example, which shows that the present invention prepares a porous hydrophilic adsorbent precursor by mixing modified bentonite and modified fly ash, starch, and sodium silicate, and then compounding them with sodium aluminate through subsequent granulation and calcination treatment, and then modifies it with chitosan and zinc oxide to prepare a hydrophilic adsorbent filler with a large specific surface area and porosity, optimizes the existing ethanol distillation and purification process, reduces the content of impurities such as moisture, methanol, acetate, etc. in the ethanol product, and prepares a high-purity industrial ethanol product.

[0127] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0128] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0129] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A purification process for preparing ethanol from synthesis gas, characterized in that: The following steps are involved: S1. Modified bentonite, modified fly ash, starch and sodium silicate are mixed uniformly and added to a reactor, deionized water is added to the reactor, and the mixture is stirred at room temperature for 30-50 min. The temperature of the reactor is increased to 70-80° C., sodium aluminate solution is added to the reactor, and the mixture is stirred for 90-110 min. The solvent is evaporated under reduced pressure to obtain a slurry having a water content of 10-20%, and the slurry is granulated and calcined to obtain an adsorbent precursor, wherein the amount ratio of the modified bentonite, modified fly ash, starch, sodium silicate, deionized water and sodium aluminate solution is 7g:3g:0.6-0.8g:3.5g: 12-14mL:10g, the sodium aluminate solution is composed of sodium aluminate and deionized water in a weight ratio of 1:9, and the roasting method is: putting the granulated particles into a muffle furnace, the temperature of the muffle furnace is increased to 95-105°C at a heating rate of 3-5°C / min, and the temperature is kept for 50-70min, the temperature of the muffle furnace is increased to 180-220°C at a heating rate of 1-3°C / min, and the temperature is kept for 30-40min, the temperature of the muffle furnace is increased to 450-550°C at a heating rate of 6-9°C / min, and the temperature is kept for 2-3h, and the temperature is naturally cooled to room temperature to obtain an adsorbent precursor; S2, adding chitosan and glacial acetic acid solution to a reactor, stirring until the system is dissolved, adding an adsorbent precursor and zinc oxide to the reactor, ultrasonically dispersing for 30-50 min, dripping sodium hydroxide solution into the reactor, ultrasonically dispersing for 40-60 min after the addition is completed, and post-processing to obtain an adsorbent filler, wherein the amount ratio of the chitosan, glacial acetic acid solution, adsorbent precursor, zinc oxide, and sodium hydroxide solution is 1-1.5g:50mL:10g:0.1-0.15g:60mL, the mass fraction of the glacial acetic acid solution is 3-5%, and the concentration of sodium hydroxide is 0.8-1.2mol / L; S3, placing an adsorbent filler on the tower plate of the distillation tower (100), so as to form an adsorbent bed layer on the tower plate of the distillation tower (100); S4, transporting crude ethanol from the feed pipe (200) to the interior of the distillation tower (100), and after purification and distillation in the distillation tower (100), the finished ethanol is discharged from the discharge pipe (300) of the distillation tower (100), the light components are discharged from the vent pipe (400) at the top of the distillation tower (100), and the heavy components collected at the bottom of the distillation tower (100) are discharged from the bottom discharge pipe (500) of the distillation tower (100); Modified bentonite is processed by the following steps: A1. Add activated bentonite and calcium oxide into a ball mill, ball mill for 40-60 min, and pass through a 100-mesh sieve to obtain a mixed powder, wherein the weight ratio of the activated bentonite to calcium oxide is 5:2; A2. Add the mixed powder and deionized water into a reactor and stir for 30-50 min at room temperature to obtain a mixture, wherein the amount ratio of the mixed powder to deionized water is 1 g:2 mL; A3. Spread the mixed material in a constant temperature and humidity chamber for 10-12 hours of heat preservation and moisture retention, and obtain modified bentonite after post-treatment, wherein the temperature of the constant temperature and humidity chamber is 65-75°C and the humidity is 50-60%; The preparation method of activated bentonite is as follows: adding bentonite and hydrochloric acid into a reactor and stirring, raising the temperature of the reactor to 75-85°C, keeping the temperature and stirring for 4-6 hours, and post-treating to obtain activated bentonite, wherein the amount ratio of the bentonite and the hydrochloric acid is 1g:10mL, and the mass fraction of the hydrochloric acid is 10-12%; The preparation method of modified fly ash is as follows: fly ash and modifying liquid are added into a reactor and stirred, the temperature of the reactor is lowered to 18-22°C, the reactor is stirred for 120-160 minutes, and the modified fly ash is obtained by post-processing, wherein the fly ash and modifying liquid are used in a ratio of 1g:15mL, and the modifying liquid is composed of sodium carbonate, sodium hydroxide and deionized water in a ratio of 5g:1g:50mL.

2. The process for purifying ethanol from synthesis gas according to claim 1, characterized in that: In step S2, the post-treatment includes: after the reaction is completed, suction filtration, washing the filter cake with purified water until it is neutral and then drying it, transferring the filter cake to a drying oven at a temperature of 90-100° C., and drying it to constant weight to obtain an adsorbent filler.

3. The process for purifying ethanol from synthesis gas according to claim 1, characterized in that: The number of plates of the distillation tower (100) is 60, the height of the adsorbent bed on each plate is 7-10 cm, one end of the feed pipe (200) extending into the distillation tower (100) is located at the top of the 13th plate from the bottom to the top, and one end of the discharge pipe (300) extending into the distillation tower (100) is located at the top of the 54th plate from the bottom to the top. The reflux ratio inside the distillation tower (100) is 60, and the distillate feed ratio is 0.105-0.

110.

4. The process for purifying ethanol from synthesis gas according to claim 1, characterized in that: In step A3, the post-treatment includes: after the treatment is completed, the temperature of the constant temperature and humidity chamber is lowered to room temperature, the material is discharged to obtain a crude modified bentonite product, the crude modified bentonite product and deionized water are added to the reactor at a dosage ratio of 1g:20mL, stirred and dispersed for 60-80min, filtered, the filter cake is rinsed with deionized water and then dried, the filter cake is transferred to a drying oven at a temperature of 60-70°C, vacuum dried to constant weight, and passed through a 100-mesh sieve to obtain modified bentonite.

5. The process for purifying ethanol from synthesis gas according to claim 1, characterized in that: The post-treatment in the preparation method of activated bentonite includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, suction filtration is performed, the filter cake is washed with purified water until it is neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 70-80°C, and dried to constant weight to obtain activated bentonite.

6. The process for purifying ethanol from synthesis gas according to claim 1, characterized in that: The post-treatment in the preparation method of modified fly ash includes: after the reaction is completed, suction filtration, washing the filter cake with deionized water until it is neutral and then drying it, transferring the filter cake to a drying oven at a temperature of 85-95°C, drying to constant weight, and passing through a 100-mesh sieve to obtain modified fly ash.

Citation Information

Patent Citations

  • Efficient adsorbent for treating volatile organic compounds in coal chemical industry production process

    CN111111619A

  • Crude alcohol purification and recovery process based on coal-based fuel ethanol

    CN118561660A